2021
DOI: 10.1101/2021.02.05.429959
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting CTP Synthetase 1 to Restore Interferon Induction and Impede Nucleotide Synthesis in SARS-CoV-2 Infection

Abstract: The newly emerged SARS-CoV-2 caused a global pandemic with astonishing mortality and morbidity. The mechanisms underpinning its highly infectious nature remain poorly understood. We report here that SARS-CoV-2 exploits cellular CTP synthetase 1 (CTPS1) to promote CTP synthesis and suppress interferon (IFN) induction. Screening a SARS-CoV-2 expression library identified ORF7b and ORF8 that suppressed IFN induction via inducing the deamidation of interferon regulatory factor 3 (IRF3). Deamidated IRF3 fails to bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 60 publications
(80 reference statements)
0
18
0
Order By: Relevance
“…As with cancer cells, depleting CTP pools via CTPS inhibition enhances the efficacy of cytidine analogs in slowing the proliferation of HIV-infected cells ( 52 ). Furthermore, a recent study revealed that two SARS-CoV-2 proteins interact with and activate CTPS1 ( 53 ). Remarkably, in addition to providing CTP necessary for SARS-CoV-2 replication, activated CTPS1 also deamidates interferon regulatory factor 3, thus suppressing interferon production and inhibiting the innate immune response ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As with cancer cells, depleting CTP pools via CTPS inhibition enhances the efficacy of cytidine analogs in slowing the proliferation of HIV-infected cells ( 52 ). Furthermore, a recent study revealed that two SARS-CoV-2 proteins interact with and activate CTPS1 ( 53 ). Remarkably, in addition to providing CTP necessary for SARS-CoV-2 replication, activated CTPS1 also deamidates interferon regulatory factor 3, thus suppressing interferon production and inhibiting the innate immune response ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study revealed that two SARS-CoV-2 proteins interact with and activate CTPS1 ( 53 ). Remarkably, in addition to providing CTP necessary for SARS-CoV-2 replication, activated CTPS1 also deamidates interferon regulatory factor 3, thus suppressing interferon production and inhibiting the innate immune response ( 53 ). Small-molecule CTPS inhibitors restore the innate immune response and suppress SARS-CoV-2 replication ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ORF8 also has an inhibitory effect on the interferon pathway (Li et al, 2020;Rao et al, 2021), and Blanco-Melo et al…”
Section: Ll Open Access Isciencementioning
confidence: 99%
“…SARS-CoV-2 propagation, infection, and viral titration were performed as previously described (54). All SARS-CoV-2 related experiments were performed in the biosafety level 3 (BSL-3) facility (USC).…”
Section: Sars-cov-2 Virus Replication and Progeny Productionmentioning
confidence: 99%